A aritmética para as escolas primárias de Mato Grosso (1910-1946) : uma análise dos documentos oficiais - Patrocínio, Margarida Célia (2016)
This thesis has as object of study the Educational legislation focusing on the elementary knowledge of Arithmetic for primary public education in the state of Mato Grosso, aiming to investigate the changes in regulations for teaching Arithmetic which set historical stages of this subject in the early school years in Mato Grosso, during the period from 1910 to 1946. For that purpose, we have tried to identify historical sources such as official documents set in the Regulations of 1910, 1927 and 1942, in the Regiments, Teaching programs, among other Reports, by creating a virtual repository. In addition, the circulation and appropriation of regulations directed to the arithmetical knowledge were analyzed, through official documents, pedagogical magazines, among others, in order to make an analysis of the modifications, according to school legislation, regarding Arithmetic in primary school in Mato Grosso. The study was developed in historical and comparative perspective, using concepts of the history of school subjects by Andre Chervel (1990); representation and appropriation by Roger Chartier (1989); document and monument by Jacques Le Goff (2003); educational legislation by Faria Filho (1998) and others. The sources were gathered with the official documents provided at Public Archives of Mato Grosso, at Barão de Melgaço Library, at Instituto Memória of the Legislative Assembly and in the database of Grupo de História, Educação e Memória (GEM). These documents are related to the subject Mathematics, presented as Arithmetic, Geometry and Design, but we are focusing our attention on Arithmetic. Thus, the state of São Paulo has emerged as a pioneer in implementing the primary education system through the School Groups, both in the construction of buildings for this purpose, as well as in the definition of regulations, teaching programs and teacher training. Thus, it was spread all over the country a model to be followed in the republican regime. In this research it was found out that the intuitive teaching remained as the pedagogical matrix for schools, that in relation to Arithmetic, there was no change in the contents of publications made in the documents, and that there were oscillations in the amount of content in the regulations, depending on the type of school which was studied, in other words, if they were School Groups, Congregated Schools or Isolated Schools they had more or less content and that the 1916 Teaching Program is based on the Teaching Program of São Paulo of 1905 and 1911. The Congregated Schools had a very important role to the school life in Mato Grosso which were made official by the Regulation of 1927 and lasted until 1952. The Arithmetic knowledge in regulations brought guidelines for teachers not to encourage memorization, but to develop a logical thinking in children, working Arithmetic more focused on the practical side of it, for everyday situations through the intuitive method. And in the worked regulations, the intuitive method prevailed officially as a teaching job for a long time. The active school took a long period of time to take part in the educational legislation and in the classroom practice, as observed in reports by the school inspectors.